Abdurauf Fitrat Created Homeland Praise (Based on Salih Bishakchi's analysis) - Ғ.М.Усмoнoв (Genius Journals, 2022)
In this article described the interpretation of Abdurauf Fitrat’s literary inheritance by foreign scholars, especially by the Turkish literary critic Salih Bishakchi.
Keywords: Drama; jaded; classical; tragedy